UPAYA MEINGKATKAN HASIL BELAJAR MATEMATIKA MATERI NILAI TEMPAT DENGAN MODEL GAME BASED LEARNING (GBL) MELALUI MEDIA ZONA BILANGAN DI KELAS I SDN 066050 MEDAN - Putri Julianti Naibaho; Indra Maryanti; Misdahlia Sasmita (STKIP Subang, 2025)
This study aims to improve the learning outcomes of Mathematics on Place Value material for class I-B SDN 066050 Medan. Based on the problems that occur in class I-B SDN 066050 Medan, the low learning outcomes of Mathematics on Place Value material are caused by the use of conventional teaching methods. The solution to overcome the problem is through the application of the Game Based Learning (GBL) learning model with the help of the Number Zone learning media. This type of research is Classroom Action Research (PTK). The subjects of this study were 14 students of class I-B SDN 066050 Medan. The object of this study is the results of student learning in Place Value material. The methods used in collecting data are observation, testing and documentation. The data analysis techniques used are quantitative descriptive and qualitative descriptive analysis techniques. The results of this study indicate that through the Game Based Learning (GBL) learning model with the help of the Number Zone learning media in learning Mathematics on Place Value material, it can improve student learning outcomes. This is evident in the pre-cycle the percentage was 28.57%, in cycle I it increased to 35.71% and in cycle II it increased to 85.71%.